EFEKTIVITAS KONSELING PENDAMPING GIZI DALAM PELAYANAN PEMENUHAN KEBUTUHAN GIZI ANAK PRA-SEKOLAH DI TK PERTIWI KOTA SUMENEP - Baitun Nur Rochma Andhini; Rifaatul Laila Mahmudah; Eka Diah Kartiningrum (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
The preschool period is an important period in children's growth and development, and good nutritional status really supports children's growth. physical growth and cognitive development. Therefore, this study aims to evaluate the effectiveness of the nutritional assistance counseling program implemented at Pertiwi Kindergarten, Sumenep City. The method used is quantitative. The type of research used was a quasi-experiment with a Nonequivalent Control Group Design. The population used in this research were Pertiwi Kindergarten students in Sumenep City in 3 classes, totaling 85 students and their parents. The results of the research explained that almost half of the respondents in the experimental group before being given counseling had knowledge at a sufficient level, whereas after being given counseling almost the majority had knowledge at a good level, namely 25 people (71.4%). Meanwhile, in the control group, it was found that the majority before being given counseling had knowledge at a sufficient level, whereas after being given time to search for information themselves there were still many who had knowledge at a sufficient level. The number of those with good knowledge only increased by 1 person to 9 people (25.7%). The results of the research were that before being given counseling, the majority of mothers and children in the experimental group had poor nutritional behavior, namely 18 people (51.4%), whereas after being given counseling the majority had good nutritional behavior. Meanwhile, the control group mostly behaved well during the pretest, while at the posttest there was a decrease in the number of respondents who behaved well, namely to 18 people (51.4%). From this research, it was concluded that there was an influence on knowledge before and after being given nutritional support counseling at Pertiwi Kindergarten, Sumenep City.